Multimodality Cardiac Imaging for Procedural Planning and Guidance of Transcatheter Mitral Valve Replacement and Mitral Paravalvular Leak Closure - Garcia-Sayan, Enrique; Chen, Tiffany; Khalique, Omar K. (Frontiers in Cardiovascular Medicine, 2021)
Transcatheter mitral valve interventions are an evolving and growing field in which multimodality cardiac imaging is essential for diagnosis, procedural planning, and intraprocedural guidance. Currently, transcatheter mitral valve-in-valve with a balloon-expandable valve is the only form of transcatheter mitral valve replacement (TMVR) approved by the FDA, but valve-in-ring and valve-in-mitral annular calcification interventions are increasingly being performed. Additionally, there are several devices under investigation for implantation in a native annulus. Paravalvular leak (PVL) is a known complication of surgical or transcatheter valve implantation, where regurgitant flow occurs between the prosthetic sewing ring and the native mitral annulus. We sought to describe the role and applications of multimodality cardiac imaging for TMVR, and PVL closure, including the use of Cardiovascular Computed Tomography Angiography and 3-Dimensional Transesophageal Echocardiography for diagnosis, prosthetic valve evaluation, pre-procedural planning, and intraprocedural guidance, as well as evolving technologies such as fusion imaging and 3D printing.